Sistem, Tantangan Dan Prospek Pendidikan Islam Di Pondok Pesantren Ribatul Muta’allimin Kota Pekalongan - Aini, Ajibah Quroti (LPTK UIN Syekh Wasil Kediri, 2022)
Islamic boarding schools are traditional Islamic educational institutions that have grown and developed in the midst of Muslim communities in Indonesia and are educational institutions that participate in educating and make a major contribution to Islamic religious education as well as in the implementation of education in Indonesia. The purpose of this article is to reveal the education system, challenges and prospects at the Ribatul Muta'allimin Islamic boarding school in Pekalongan City. This research uses field qualitative methods at the Ribatul Muta'allimin Islamic Boarding School, Pekalongan City. The results of this study found that the pesantren education system is basically a traditional Islamic boarding school education system, where students live together and study religious knowledge under the guidance of a kyai. Islamic boarding schools as Islamic educational institutions in Indonesia also have big challenges such as modernity and radical Islam which continues to develop in Indonesia, especially at the MA Ribatul Muta'allimin Islamic boarding school in Pekalongan City, especially in the Islamic education environment. Moderate Islam that is coveted by Muslims, namely Islam that is friendly and not easily angered, is a teaching that will always be taught in Islamic boarding schools as Islamic educational institutions.